Analysis of the psychiatric consultations requested for hospitalized COVID-19 patients: One year results from a major pandemic hospital - YORGUNER, NEŞE (My University, 2022)
Background/Aim: Coronavirus 2019 (COVID-19) has brought unprecedented challenges to the practice of consultation-liaison psychiatry. Moreover, it is probable that the characteristics of psychiatric consultations and administered treatments have varied and will continue to vary significantly over time. Given the relative lack of prior research concerning this issue, this study aimed to provide a multidimensional analysis of the psychiatric consultations requested for inpatients diagnosed with COVID-19 and to examine the temporal course of the selected variables throughout the pandemic. Methods: In this retrospective cohort study, the medical records of 232 patients who underwent psychiatric consultation between May 1, 2020 and April 30, 2021 were reviewed in detail. Data were obtained for a series of variables, including reasons for consultation, diagnoses after assessment, medical comorbidities, past psychiatric history, treatment arrangements, and clinical outcomes, after which the data were systematically classified to be included in the multi-dimensional analysis. Results: The mean age of the patients was 66.79 (17.18) years (61.21% were males). The most common reasons for consultation were psychomotor agitation, anxiety, and treatment non-compliance, while adjustment disorder and delirium were the most common diagnoses after psychiatric evaluation. Among the reasons for consultation, the shortest durations from admission to consultation were associated with psychomotor agitation, assessment for drug interaction, and treatment non-compliance while among the diagnoses, the duration was shortest for dementia, mental retardation, bipolar disorder, and psychosis. The most frequently prescribed medications were antipsychotics, antidepressants, and benzodiazepines. The number of consultations and rates of delirium and death showed a significant increase over the course of the study. Delirium and medical comorbidities were found to be the strongest predictors of death as a clinical outcome. Conclusion: Knowledge and experience in the field of consultation-liaison psychiatry might contribute to the accurate diagnosis of COVID-19-related neuropsychiatric syndromes in addition to implementation of appropriate treatment interventions
Keywords: COVID-19; Consultation-liaison psychiatry; Neuropsychiatry; Psychopharmacology; Delirium; Adjustment disorder